1993
DOI: 10.1021/bc00023a005
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activities of a cephalosporin prodrug in combination with monoclonal antibody-.beta.-lactamase conjugates

Abstract: 7-(Phenylacetamido)cephalosporin mustard (CM) and 7-(4-carboxybutanamido)cephalosporin mustard (CCM) were developed as anticancer prodrugs that could be activated site selectively by monoclonal antibody-beta-lactamase conjugates targeted to antigens present on tumor cell surfaces. Both CM and CCM were hydrolyzed by purified beta-lactamases from Escherichia coli (EC beta L), Bacillus cereus (BC beta L), and Enterobacter cloacae (ECl beta L). This resulted in the release of phenylenediamine mustard (PDM), a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 18 publications
3
48
1
Order By: Relevance
“…Cytotoxicity Assays-The LD 50 of the phenylenediamine mustard parental drug (PDM) and the 7-(4-carboxibutamido)-cephalosporin mustard prodrug (CCM) were determined by incubating 10 6 T. brucei brucei AnTat 1.1 parasites (2.5 h, 30°C) in phosphate-saline-glucose buffer with PDM or CCM (0 -150 M) (26).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxicity Assays-The LD 50 of the phenylenediamine mustard parental drug (PDM) and the 7-(4-carboxibutamido)-cephalosporin mustard prodrug (CCM) were determined by incubating 10 6 T. brucei brucei AnTat 1.1 parasites (2.5 h, 30°C) in phosphate-saline-glucose buffer with PDM or CCM (0 -150 M) (26).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, both the binding of the VHH and the enzymatic activity of the ␤-lactamase are well preserved in the fusion protein. The ␤-lactamase can also convert the mustard (CCM) into the highly toxic PDM (26). A 2.5 h incubation of 0 to 150 M CCM to bloodstream form T. brucei AnTat 1.1 parasites in PSG buffer revealed an LD 50 value of 20 M for this prodrug, which is 20ϫ higher than the parental drug PDM (Fig.…”
Section: Efficacy Of Cab-an33 As Molecular Recognition Unit In a Bifumentioning
confidence: 96%
See 1 more Smart Citation
“…CM was 50-fold less cytotoxic toward human lung adenocarcinoma cells than phenylenediamine mustard, whereas after activation by a monoclonal antibody-␤-lactamase conjugate, cytotoxicity was comparable (Svensson et al, 1992). The CM analog 7-(4-carboxybutanamido)-cephalosporin mustard (CCM) was also shown to be activated to phenylenediamine mustard by ␤-lactamases with K m values in the micromolar range (Vrudhula et al, 1993b). CCM was less toxic than the parent drug phenylenediamine mustard toward human lung cancer cells, and prodrug activation was observed after coadministration with an enzyme immunoconjugate consisting of ␤-lactamase and the monoclonal antibody L6 that binds to antigens on lung adenocarcinoma cells.…”
Section: ␤-Lactamasementioning
confidence: 99%
“…CCM was less toxic than the parent drug phenylenediamine mustard toward human lung cancer cells, and prodrug activation was observed after coadministration with an enzyme immunoconjugate consisting of ␤-lactamase and the monoclonal antibody L6 that binds to antigens on lung adenocarcinoma cells. In mice bearing lung adenocarcinoma cells, phenylenediamine mustard was ineffective, whereas a significant antitumor activity was observed using CCM and an enzyme immunoconjugate containing ␤-lactamase (Vrudhula et al, 1993b). In a subsequent study, it was shown that CCM was even more effective than C-DOX in mice bearing human melanoma tumor cells (Kerr et al, 1995), and CCM was more recently shown to be effective in renal cell carcinoma and human lung carcinomas using ADEPT approaches (Svensson et al, 1998;.…”
Section: ␤-Lactamasementioning
confidence: 99%